Being a Pakistani mother in Catalonia: a mixed methods study - Maryam El Khayat; Magda Rivero; M. Teresa Anguera (Frontiers in Psychology)
IntroductionIn Pakistani migrant families, contextual transformation can affect adult caregivers’ parental skills and their ability to exercise positive parenting. We focused on identifying and describing patterns, practices and beliefs about parenting, identifying differential characteristics between the context of origin and the host context, and exploring Pakistani immigrants’ use of resources or assets in the area of parenting support.MethodsParticipants consisted of 20 women, established in Catalonia, Spain (<5 years of residence) who have children (at least one of preschool-age). We used a method of indirect observation based on verbal narrative data and textual material that allows integration between qualitative and quantitative elements. The analysis of polar coordinate (quantitative) was applied to obtain a map of interrelationships between codes/categories, based on code matrices. This method is innovative as this is the first study we know in which focus groups have been analyzed through polar coordinate.ResultsOur findings underscore the importance of examining in-depth the concept of family, parenting and upbringing from a cross-cultural perspective. Our results suggest that Pakistani migrant mothers dedicate resources and efforts to maintain the values and practices of origin, and to transmit them to the following generations.DiscussionConstant communication among relatives using new technologies, the desire to return to Pakistan, and the absence of spaces for interaction between native and migrated families facilitate the maintenance of the upbringing model of origin and resistance to change. A nuclear family structure and access to educational and health services promote acculturation processes in favor of adaptation to the new reality.